The concept of tribal society (Vol.5) - Pfeffer,Georg (ed.); Behera,Deepak Kumar (ed.) (New Delhi, 1997)
Documentation of various facets of tribal social reality is very much essential before they are totally eclipsed by the rapid process of globalization of the world economy. While examining the current literature on tribal societies we notice a curious absence of scientific studies based on intensive fieldwork among a large and important section of the world population. The series Contemporary Society: Tribal Studies tries to fill in this gap and thereby attempts to remove our ignorance on many aspects of tribal world. The ongoing series has already brought out four earlier volumes, namely, (1) Structure and Process, (2) Development Issues, Transition and Change, (3) Social Concern and (4) Social Realities. The present volume The Concept of Tribal Society, deals with an important issue of defining the tribal society. It points out that the traditional criteria for defining the tribal society are no longer valid in the context of rapid social change and transformation. Thus the concept (3z(BTribal Society(3y (Bis a flexible one and the contexts of time and space are important considerations for the understanding of such a concept. The volume covers many empirical studies covering tribal people of both South Asia and abroad for a better understanding of the problem of defining (3z(BTribal Society.(3y (BIt becomes essential for the social scientist to formulate the necessary perceptive while dealing with such a definitional problems
Keywords: Tribes-India